2021
DOI: 10.33711/yyuefd.959827
|View full text |Cite
|
Sign up to set email alerts
|

Tartışmalarla Zenginleştirilmiş Tahmin Et-Gözle-Açıkla (TGA) Destekli Fen Laboratuvar Uygulamalarının Öğretmen Adaylarının Akademik Başarılarına Etkisi

Abstract: The purpose of this study was to investigate effectiveness of Predict-Observe-Explain (POE) enriched with discussions based laboratory on pre-service science teachers' academic achievement. For this purpose, fundamental science concepts were dealt with in the research. In the study, a quasi-experimental model was utilized and a total of 46 pre-service science teachers were selected as the sample. Two randomly selected groups, one of which was experimental (n = 22) and the other was control (n = 24) were used i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…The overall effect size of the study was found to be at a high level. The results of this study are supported by many studies in the literature (Koray et al, 2007, Bilen, 2009Arı ve Bayram, 2012;Bozkurt, 2012;Karatekin, 2012;Yurdatapan, 2013;Gezer, 2014;Kırılmazkaya, 2014;Aslan, 2016;Baydere ve Çakır, 2019;Köseler, 2019;Barut, 2020;Coştu, 2021;Kırıktaş ve Kesercioğlu, 2021;Mukagihana et al, 2022;Wola et al, 2023) is compatible with the results.…”
Section: Discussionsupporting
confidence: 86%
“…The overall effect size of the study was found to be at a high level. The results of this study are supported by many studies in the literature (Koray et al, 2007, Bilen, 2009Arı ve Bayram, 2012;Bozkurt, 2012;Karatekin, 2012;Yurdatapan, 2013;Gezer, 2014;Kırılmazkaya, 2014;Aslan, 2016;Baydere ve Çakır, 2019;Köseler, 2019;Barut, 2020;Coştu, 2021;Kırıktaş ve Kesercioğlu, 2021;Mukagihana et al, 2022;Wola et al, 2023) is compatible with the results.…”
Section: Discussionsupporting
confidence: 86%